1981
DOI: 10.1021/jf00107a050
|View full text |Cite
|
Sign up to set email alerts
|

Studies on desi and kabuli chickpea (Cicer arietinum L.) cultivars. 3. Mineral and trace elements composition

Abstract: Table I), was below their detection limit. All the materials tested except the beverages were analyzed for recovery of spiked levels of M e a 0 and Me2S02. In all cases including spiked blanks, the recovery was in the range of 90-100%. The reproducibility of the method was found to be in the range of 10-15%. Me2S0 and Me#02 were not detected in the solvents or distilled water blanks. The detection limit of Me2S0 and Me2S02 was 1.2 ng at a signal-to-noise ratio of 2. This was similar to the value determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
32
4

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 3 publications
13
32
4
Order By: Relevance
“…The crude protein of C. maritima and C. cathartica were higher than common pulses reported by Gupta and Wagle (1978), Jambunathan and Singh (1980), Nwokolo (1987) and Nwokolo and Oji (1985). The protein was also higher than Canavalia ensiformis (30.62%), Canavalia gladiata (27.48%) (Rajaram & Janardhanan, 1992) and C. maritima (27.3%) (Abbey & Ibeh, 1987), Neonotonia wightii (20.6%) (Viswanathan, Thangadurai, & Ramesh, 2001).…”
Section: Chemical Propertiesmentioning
confidence: 74%
“…The crude protein of C. maritima and C. cathartica were higher than common pulses reported by Gupta and Wagle (1978), Jambunathan and Singh (1980), Nwokolo (1987) and Nwokolo and Oji (1985). The protein was also higher than Canavalia ensiformis (30.62%), Canavalia gladiata (27.48%) (Rajaram & Janardhanan, 1992) and C. maritima (27.3%) (Abbey & Ibeh, 1987), Neonotonia wightii (20.6%) (Viswanathan, Thangadurai, & Ramesh, 2001).…”
Section: Chemical Propertiesmentioning
confidence: 74%
“…utilis are found to contain high level of crude protein (26.25-29.6%) [29][30][31]. This value seems to be higher than that of commonly consumed pulses like chickpea, pigeon pea, green gram, black gram, and red gram [32][33][34]. Siddhuraju et al [2] reported that the dehulled seeds exhibit higher protein content (30.3-33.5%) than the whole beans (24.3-29.8%).…”
Section: Biochemical Compositionmentioning
confidence: 99%
“…The Desi cultivars have small and wrinkled seeds with brown, black or green colour (Kaur & Singh, 2005). Significant differences in these two groups have been observed with regard to their seed coat percentage, crude fibre content, mineral, trace element composition, polyphenolic content and in vitro digestibility (Chavan, Kadam, & Salunkhe, 1986;Jambunathan & Singh, 1981). Chavan et al (1986) related the concentration of crude fibre with seed coat content.…”
Section: Introductionmentioning
confidence: 99%